Effect of Selected Metal Ions on the Mycelial Growth of Sclerotinia Sclerotiorum Isolated from Soybean Field in Rongai, Kenya - Mwangi, Erastus S.K; Gatebe, Erastus G; Ndung’u, Mary W (International Journal of Chemistry and Materials Research, 2014)
White mold caused by Sclerotinia sclerotiorum attacks a wide host range of broad-leafed plants which includes soybeans. The effect of twelve metal ions (Hg+2, Co+3, Ag+1, La+3, Cd+2, Cr+3, Cu+2, Zn+2, Mo+5, Sr+2, Sn+4 and Ba+2) on the growth of pathogenic fungus S. sclerotiorum was studied. The fungus was isolated from infected soybean plant collected at Rongai, Kenya. The isolate was tested for the tolerance to metal ions at concentrations of 50.0, 100.0, 250.0 and 500.0 ppm amended into the C: N (35:1) glucose peptone prepared using 1.5% (3.75g) agar culture medium. All the investigated metal ions exhibited concentration dependent mycelial growth using disc diffusion test. Of 12 metal cations tested, only copper and zinc stimulated mycelial growth of S. sclerotiorum mycelial in relatively higher concentrations. Higher concentrations of Hg+2, Ag+1, La+3 and Cd+2 inhibited growth of fungi causing an opaque halo in the medium. FT-IR spectral analysis of culture filtrate reviewed oxalic acid secreted precipitated primarily as oxalate at the periphery of the fungal colony. This work suggests that strong pollution of soil by some heavy metals could be a restrictive factor of development and pathogenicty of S. sclerotiorum fungi in the environment.